2015
DOI: 10.2147/dddt.s90147
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curcumin and its nanoformulation on adjuvant-induced arthritis in rats

Abstract: BackgroundRheumatoid arthritis (RA), induced by the prolonged inappropriate inflammatory responses, is one of the most prevalent of all chronic inflammatory joint diseases. Curcumin (CM), a yellow hydrophobic polyphenol derived from the herb turmeric, has various pharmacological activities against many chronic diseases and acts by inhibiting cell proliferation and metastasis and downregulating various factors, including nuclear factor kappa B, interleukin-1β and TNF-α. Given the pathogenesis of RA, we hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Results of a meta-analysis of randomized clinical trials (RCTs) concerning turmeric extracts containing curcumin in patients with arthritis suggested that turmeric extract (about 1000 mg/day of curcumin) alleviated pain symptoms connected with arthritis [ 35 ]. Moreover, in a study by Zheng et al [ 36 ], curcumin was shown to decrease the expression of NF-κB, TNF-α, and IL-1β in the synovial fluid and blood serum. Since the observed effects were similar to effects observed in a standard regimen with methotrexate, the authors of the study speculated that curcumin could be used as anti-rheumatic therapy either in monotherapy or as an adjuvant in RA patients.…”
Section: The Benefits Of Polyphenols’ Consumption In Rheumatoid Arthrmentioning
confidence: 99%
“…Results of a meta-analysis of randomized clinical trials (RCTs) concerning turmeric extracts containing curcumin in patients with arthritis suggested that turmeric extract (about 1000 mg/day of curcumin) alleviated pain symptoms connected with arthritis [ 35 ]. Moreover, in a study by Zheng et al [ 36 ], curcumin was shown to decrease the expression of NF-κB, TNF-α, and IL-1β in the synovial fluid and blood serum. Since the observed effects were similar to effects observed in a standard regimen with methotrexate, the authors of the study speculated that curcumin could be used as anti-rheumatic therapy either in monotherapy or as an adjuvant in RA patients.…”
Section: The Benefits Of Polyphenols’ Consumption In Rheumatoid Arthrmentioning
confidence: 99%
“…A threefold increase in maximum plasma concentration and the area under the plasma drug concentration-time curve (AUC) was observed when comparing curcumin in NEs to curcumin suspensions. Oral administration of curcumin-NEs significantly decreased TNF-α and IL-1β levels in both synovial fluid and blood serum (Table 1) [13]. It is therefore concluded that the formulation of NEs significantly enhanced curcumin absorption.…”
Section: Food Components As Delivered Drugs Tomentioning
confidence: 82%
“…The expansion of an emulsifier is necessary for producing droplets with smaller size because it reduces the interfacial tension and surface energy in unit range between the oil and water phases of the emulsion. NEs show advantages in high drug-loading capacity [12], core-shell protection of embedded drugs from physicochemical and enzymatic degradation [8], wide drug distribution along the GI tract, prolonged drug release due to large surface area [7], and ease of preparation [13]. A threefold increase in maximum plasma concentration and the area under the plasma drug concentration-time curve (AUC) was observed when comparing curcumin in NEs to curcumin suspensions.…”
Section: Food Components As Delivered Drugs Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes can differentiate into macrophages, which play a pivotal role in the induction and progression of inflammatory processes (Liu et al, ). Paeoniflorin; astragaloside IV; esculentic acid; hesperidin; 7′‐(3′,4′‐dihydroxyphenyl)‐ N ‐[(4‐methoxyphenyl)ethyl]propenamide; sinomenine; tetrandrine; curcumin; methyl benzoate‐2‐ O ‐β‐ d ‐xylopyranosyl(1‐2)[ O ‐β‐ d ‐xylopyranosyl(1‐6)]‐ O ‐β‐ d ‐glucopyranoside; methyl benzoate‐2‐ O ‐β‐ d ‐xylopyranosyl(1‐6)‐ O ‐β‐ d ‐gluco‐pyranoside; polyphyllin I, 9,9′‐ O ‐di‐( E )‐feruloyl‐meso‐5,5′‐dimethoxysecoisolariciresinol; cimifugin; 1‐ethoxy‐3,7‐dihydroxy‐4,6‐dimethoxy‐9‐fluorenone; triptolide; celastrol; anhuienoside C; artemisinin; and (−)‐epicatechin‐3‐ O ‐β‐ d ‐allopyranoside can inhibit the macrophages‐mediated inflammatory processes in the joints of RA model (Cai, Zheng, Shang, & Zhao, ; Fan et al, ; Gao et al, ; Han et al, ; Hsiao, Wu, & Lin, ; Hu et al, ; Lee, Lee, Kim, & Lee, ; Li, Li, Cai, Hu, & Zhang, ; Lin et al, ; Lin et al, ; Liu et al, ; Liu et al, ; Matta et al, ; Niu et al, ; Wang et al, ; Wang et al, ; Wang & Chen, ; Yang et al, ; Yi et al, ; Zhang et al, ; Zhou et al, ). Following maturation, the lymphocytes enter the circulation and peripheral lymphoid organs (spleen and lymph nodes).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%